ILMU SKIL VERSI HADIS RASUL (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2016)
Angel of Jibril submit apocalipse to Prophet of Muhammad is obliged to be knocked by heart that way sunnah juag. Prophet of Muhammad isobliged to submit him to its Friend iswho him him it on that. Friend accompanying itisobliged to submit him it to other friend, application of hadis submit from me although one sentence, and obligation of us isto submit non hushing its membership. That way further hitherto ought to. Hence him all friend there iscapable to work uisa 15 year. Non reached by impossible of SDM ready to work age 15 year. Make inwrought curriculum among between informal formal education and nonformal. All required prodi isobliged to there isissame module, each;every module there must be result of record and entered included to issame website. Each;Every prodi isobliged to 50 % education of religion as according to student religion. Transfer all PNS and non PNS woman become informal Teacher. Labouring comparison of Teacher and maximal pupil 1:10. Opening required prodi so that to be reached byage 15 year of is who is job activity . To which not yet will ready to work to continue to next ladder, as researcher energy to ladder in its its his. Government ready to promise to to open required byemployment islocal opened prodi